Path toward the Top Leadership: A Network Analysis of the Civil Service System in the Early Southern Song (1131– 1164) - Xiong, Huei-Lan (Journal of Historical Network Research, 2022)
This study takes a network approach to explore the career trajectories of Song officials who served in the Imperial Library from 1131 to 1164. It elucidates the fact that the officials’ career records, abundant in Chinese historical sources, are a trove of information that we may utilize to decipher the operations of the state administration and the life courses of the officials. “Nurturing talent in the scholarly institutes” was a policy that the Song dynasty implemented to cultivate high-ranking court officials for its civilian leadership. The practice scheme of “talent-nurturing” involved appointments to certain government offices which were distributed throughout the entire bureaucracy, and those to Imperial Library in particular were viewed as the launchpad for career prosperity. Since government agencies were functionally interlocked with one another and officials were frequently transferred from office to office in a perplexing but sequential manner, these features (connectivity and directedness) naturally lend themselves to network analysis. Using the career records of officials in the early Southern Song Imperial Library, this paper constructs a directed network of bureaucratic rotations. It demonstrates that offices covered by the “talent-nurturing” scheme were stepping-stones towards the top echelon of government and their missions concerned evaluation of historical or contemporary figures’ behavior and character in different aspects. By focusing on the early Southern Song when the dynasty was embroiled in war and political instability, this paper also illuminates how crises impacted the implementation of this “talent-nurturing” policy.